2005
DOI: 10.1088/6102/44/3/505
|View full text |Cite
|
Sign up to set email alerts
|

Solving Solar Neutrino Puzzle via LMA MSW Conversion

Abstract: We analyze the existed solar neutrino experiment data and show the allowed regions. The result from SNO's salt phase itself restricts quite a lot the allowed region's area. Reactor neutrinos play an important role in determining oscillation parameters. KamLAND gives decisive conclusion on the solution to the solar neutrino puzzle, in particular, the spectral distortion in the 766.3 Ty KamLAND data gives another new improvement in the constraint of solar MSW-LMA solutions. We confirm that at 99.73% C.L. the hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Following the tradition [15,16], we first analyzed the data with a standard least-squares analysis (often called "χ 2 analysis"). In our analysis, the least-squares function for each type of solar neutrino experiment is…”
Section: Standard Least-squares Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the tradition [15,16], we first analyzed the data with a standard least-squares analysis (often called "χ 2 analysis"). In our analysis, the least-squares function for each type of solar neutrino experiment is…”
Section: Standard Least-squares Methodsmentioning
confidence: 99%
“…In the framework of neutrino oscillations, a standard least-squares analysis method is usually adopted to analyze the data in the context of Frequentist Statistics [15,16]. These analyses have shown that the solar neutrino problem is solved by the LMA solution.…”
Section: Introductionmentioning
confidence: 99%
“…Traveling through the decreasing solar matter potential, the ν e 's undergo a resonant conversion to ν µ , emerging from the Sun mainly as ν µ 's. The effect is named after its discoverers Mikheyev, Smirnov and Wolfenstein (MSW) [6].…”
Section: Pos(hql 2010)057mentioning
confidence: 99%
“…It is mass differences not masses that are the crucial points of this problem. However neutrino oscillation experiments, e.g., solar and atmospheric neutrino oscillations have confirmed the mass differences between different neutrinos [1,2,3,4,19,20], thus this problem cannot be neglected.…”
Section: Iii1 Negative Energy Neutrinosmentioning
confidence: 99%